First-principles study of monolayer Be2C as an anode material for lithium-ion batteries - Yeoh, Keat Hoe; Chew, Khian Hooi; Chu, Y.Z.; Yoon, T.L.; Rusi, -; Ong, D.S. (AIP Publishing, 2019)
In this work, the feasibility of a monolayer Be2C as the anode material for lithium-ion battery (LiB) was investigated using the density functional theory. Our study reveals that the adsorption of Li atoms changes the electronic conductivity of a monolayer Be2C from semiconducting to metallic. This resulted in a low Li diffusion barrier of 0.11 eV, which is highly needed for the fast charge and discharge processes of the LiB. Additionally, the predicted open-circuit voltage was 0.33 V, and the calculated maximum theoretical capacity was impressively high (1785 mAh/g). Our findings suggest that the monolayer Be2C is a promising anode material for high-performance LiB.